45 years [videorecording (DVD)] - Haigh, Andrew, 1973-; Rampling, Charlotte, 1946-; Courtenay, Tom; Wells, Dolly, 1971-; Constantine, David, 1944- (Paramount Home Entertainment, 2016)
As Kate and Geoff prepare to celebrate their 45th wedding anniversary, their marriage is shaken when unexpected news threatens to change their lives.